Responding to the Plague According to the Hadith Perspective in the MUI Fatwa - Muhamad Nazri Hauqal; Romlah Abu Bakar; Abdul Ghofur (Penerbit Hellow Pustaka, 2025)
This research discusses the hadith related to the outbreak contained in the MUI fatwa. As time goes by, hadith has become an important foundation in selecting references as strong and accurate references. This is one of the reasons for the MUI fatwa. Therefore, the MUI fatwa quotes several verses from the Koran and hadith as a reference to be used as a basis for the outbreak that occurred in 2020. As time goes by, the text of the hadith is interpreted according to needs. Therefore, it is necessary to understand hadith that is in accordance with the needs for using the hadith